Sportif.App as an Effort to Increase Sports Human Resources Readiness and Digitalization of Sports Data Information Management - Fatkhul Imron; Joko Sulistyono; Moh Erkamim; Zandra Dwanita Widodo (Pusat Riset dan Inovasi Nasional, 2023)
This research is a continuation of community service activities entitled